Direct foreign investments and the lack of positive effects on the economy - Suzana Djordjevic; Zoran Ivanovic; Sinisa Bogdan (UTMS Journal of Economics, 2015)
In recent years, Croatia was interesting to investors in attracting foreign direct investment. One of the objectives of this research was to deal with their negative effects. Most of invested capital was invested in brownfield investments, i.e. in taking over the ownership share of companies through privatization. Consequently, revenues were spent to settle financial debts and not on the growth and development of competitiveness. According to economic theory, foreign direct investments have a positive impact on the economic growth of the recipient country. This paper attempts to answer the question: "Is the economic theory confirmed in the Croatian case?" The aim is to analyse the impact of foreign direct investments on the economic growth of Croatia in the period from 1999 to 2014. The paper analyses the impact that direct foreign investments had on the unemployment rate, GDP per capita and export using the model of linear regression.
Keywords: F21; E20; 330; foreign direct investments; employment; exports